Alginate Hydrogel Microencapsulation Inhibits Devitrification and Enables Large‐Volume Low‐CPA Cell Vitrification. (15th October 2015) - Huang, Haishui; Choi, Jung Kyu; Rao, Wei; Zhao, Shuting; Agarwal, Pranay; Zhao, Gang; He, Xiaoming
Abstract : Cryopreservation of stem cells is important to meet their ever‐increasing demand by the burgeoning cell‐based medicine. The conventional slow freezing for stem cell cryopreservation suffers from inevitable cell injury associated with ice formation and the vitrification (i.e., no visible ice formation) approach is emerging as a new strategy for cell cryopreservation. A major challenge to cell vitrification is intracellular ice formation (IIF, a lethal event to cells) induced by devitrification (i.e., formation of visible ice in previously vitrified solution) during warming the vitrified cells at cryogenic temperature back to super‐zero temperatures. Consequently, high and toxic concentrations of penetrating cryoprotectants (i.e., high CPAs, up to ≈8m ) and/or limited sample volumes (up to ≈2.5 μL) have been used to minimize IIF during vitrification. It is revealed that alginate hydrogel microencapsulation can effectively inhibit devitrification during warming. The data show that if ice formation were minimized during cooling, IIF is negligible in alginate hydrogel microencapsulated cells during the entire cooling and warming procedure of vitrification. This enables vitrification of pluripotent and multipotent stem cells with up to ≈4 times lower concentration of penetrating CPAs (up to 2m, low CPA) in up to ≈100 times larger sample volume (up to ≈250 μL, large volume). Abstract : Alginate hydrogel microcapsules are exceptional in inhibiting devitrification in cryopreserved samples during warming, which enables cryopreservation by vitrification in ≈100 times larger volume using a low and nontoxic concentration of cryoprotectants (i.e., low CPAs) and makes it possible to practically use the low‐CPA vitrification technology for cryopreserving stem cells.